Holography for BCFTs with multiple boundaries: multi-splitting quenches - Joseph Dominicus Lap; Berndt Müller; Andreas Schäfer; Clemens Seidl (Journal of High Energy Physics)
Abstract We elaborate on the method introduced in arXiv:2403.02165 for holographic duals of Boundary Conformal Field Theories (BCFTs) with multiple boundaries. Naïvely, as the number of boundaries grow large such a calculation becomes unmanageable. We show that is not always the case. Using these advances we calculate the entanglement entropy as a function of time for 1+1-dimensional CFTs that are split into N subsystems. We give explicit results for N = 4 and N = 17. We find that all qualitative differences that arise for larger N are present N = 4.